Higher-order thinking skills in e-learning contexts in higher education: a phenomenological study - Khadka, Jiban; Dahal, Niroj; Acharya, Usha; Puri, Gobinda; Subedi, Nirmala; Hasan, Md. Kamrul (Frontiers in Education, 2025)
Teaching and learning activities are primarily conducted through in-person classes and assessed by periodic examinations, with little emphasis on developing higher-order thinking skills (HOTS) in Asian territories and Nepal. In higher education, there is inadequate literature on the practice of HOTS in online and remote learning modes. Using a phenomenological approach, this study investigated how students experience and develop HOTS within the e-learning context of higher education in Nepal. Four students from an open and distance university were purposefully chosen for data collection. These students had been enrolled in online classes for at least one semester at the Bachelor’s, Master’s, or MPhil levels. With their consent, in-depth interviews using semi-structured, open-ended questions were arranged for approximately 1 h and conducted online in Zoom. The analysis involved coding and condensing the interview data into themes, which were then discussed in relation to the relevant literature. The findings indicate that the university manages its virtual classes in a blended mode, using both synchronous and asynchronous methods with limited e-resources such as MS Teams and Moodle. These platforms are used for innovative teaching approaches to strengthen HOTS, such as critical thinking, problem-solving, intercultural communication, and social networking. Teaching approaches included tutor lectures, student self-exploration, peer learning, collaboration, and networking. A significant finding was the gradual shift from tutor-led instruction to self-directed and self-motivated learning. The study concluded that e-learning in higher education has a notable transformative impact on developing HOTS and its application to students’ personal and professional development.